IMPROVING STUDENTS’ LANGUAGE SKILLS THROUGH NEW INTEGRATED APPROACHES IN MODERN LANGUAGE TEACHING (Journal of Universal Science Research, 2025)
The study refers to creative solutions for enhancing students' language skills by incorporating new pedagogies. Traditional methods fail to address differentiated learning needs and modern demands such as application in everyday life and fluency. The study proposes the use of technology-based learning, inter-disciplinary pedagogy, and experiential training to create speaking, listening, reading, and writing abilities.